New Approaches in Viticulture: Different Rates of Net Shadow Applications to Yield, Must, Color and Wine Quality - Tuba Uzun Bayraktar (Horticulturae)
This study was conducted on the Sinceri grape variety in 2023. Three applications (35%, 55% and 75% net shadows) and a control were applied in the experiment. The shading materials were covered over the vines when the grapes were at veraison. The effects of the applied net shadows on the grape yield, color parameters of the berry skin and physicochemical analyses in the must were examined. In addition, some chemical analyses [such as pH, ethyl alcohol (%), volatile acidity (mg/L), reducing sugar (g/L), density and total acidity (g/L)], secondary metabolites, color parameters and sensory analyses were performed in wines produced spontaneously by the microvinification method. In terms of the yield parameters, the 55% net shadow application provided a 61.93% increase in grape yield, 37.83% increase in cluster weight and 35.76% increase in 100-berries weight compared to the control. While the L* value and Hue angle increased, the a* value, b* value and Chroma value decreased as the proportion of shading material increased. In the must, the must yield and total acidity increased while the TSSC, maturity index and density decreased. In terms of the physicochemical wine analysis (ethyl alcohol, density, total phenolic compound and antioxidant amount) and sensory evaluations, the best result was given by 75% net shadow and, in terms of wine color parameters, by 55% net shadow application.